Analysis of healthcare-related postpartum infections in the Campos Gerais region: cesarean versus vaginal delivery (Research, Society and Development, 2022)
Postpartum infections are a significant cause of prolonged hospitalization and maternal morbidity and mortality, with cesarean delivery being one of the main risk factors. This is a retrospective cross-sectional study, in which the medical records of patients affected with postpartum infection in the years 2019 to 2021 at the Hospital Universitário Regional Wallace Thadeu de Mello e Silva / Hospital Universitário Materno Infantil in Ponta Grossa were evaluated. During this period, 9097 obstetric procedures were performed, and 58 cases of obstetric infections were recorded, resulting in a rate of 0.63%, going from a rate of 1.5% (45 notifications) in 2019 to 0.27% (8) in 2020 and 0.15% (5) in 2021. The rate of healthcare-associated infections in cesarean sections was 1.78%, and showed a decrease, being 5.26% in 2019 and falling to 0.63% in 2020 and 0.27% in 2021, while the rate in vaginal delivery remained similar in the three years studied (0.11% in 2019 and 0.12% in 2020 and 2021). Among these, 79.31% were wound infections, while 12.06% were endometritis infections. It is concluded that performing cesarean sections predisposes to a higher risk of postpartum infection, especially if performed after the onset of labor. Moreover, there was a progressive increase in the cesarean rate over the years studied, reaching 40.85% in 2021, considerably higher than that recommended by the World Health Organization.